On-line Integration of Semantic Information from Speech and Gesture: Insights from Event-related Brain Potentials - Özyürek, Aslı; Willems, Roel M.; Kita, Sotaro; Hagoort, Peter (Journal of cognitive neuroscience, 2007)
During language comprehension, listeners use the global semantic representation from previous sentence or discourse context to immediately integrate the meaning of each upcoming word into the unfolding message-level representation. Here we investigate whether communicative gestures that often spontaneously co-occur with speech are processed in a similar fashion and integrated to previous sentence context in the same way as lexical meaning. Event-related potentials were measured while subjects listened to spoken sentences with a critical verb (e.g., ), which was accompanied by an iconic co-speech gesture (i.e., KNOCK). Verbal and/or gestural semantic content matched or mismatched the content of the preceding part of the sentence. Despite the difference in the modality and in the specificity of meaning conveyed by spoken words and gestures, the latency, amplitude, and topographical distribution of both word and gesture mismatches are found to be similar, indicating that the brain integrates both types of information simultaneously. This provides evidence for the claim that neural processing in language comprehension involves the simultaneous incorporation of information coming from a broader domain of cognition than only verbal semantics. The neural evidence for similar integration of information from speech and gesture emphasizes the tight interconnection between speech and co-speech gestures.